Principal Leadership Style and Teacher Performance in Improving Learning Quality - Syawal Kurnia Putra (Punggawa Legacy Center, 2026)
School improvement efforts often failed to translate policy expectations into consistent classroom practice, making leadership style a practical concern for learning quality. This study examined how principal leadership styles related to teacher performance and how that relationship supported the improvement of learning quality. A qualitative library-based design was used, relying on secondary sources from peer-reviewed scholarship on instructional leadership, transformational leadership, accountability practices, supervision and feedback, professional development, and school climate. The analysis synthesized recurring mechanisms that connected leadership to teacher work and classroom processes. The findings indicated that leadership influenced learning quality primarily through teacher performance by clarifying instructional direction, strengthening supervision and feedback, supporting professional capacity, and shaping a school climate that encouraged accountability and collaboration. Instructional leadership provided the most direct pathway to improving teaching practice, while transformational and democratic elements strengthened motivation and shared commitment when aligned with clear standards. Transactional elements supported baseline discipline but were insufficient as a dominant approach for instructional improvement. The study concluded that a balanced leadership profile anchored in instructional priorities was most consistent with sustained improvements in learning quality.